Guru Inovatif dan Kreatif Berbasis Kearifan Lokal Menggunakan Aplikasi CANVA - Perdana, Indra; Theasy, Yoan; Veniaty, Syarah; Winata, Rahmat; Rizaldi, Muhammad (Jurnal Pengabdian Kampus, 2024)
Innovative and creative teachers can be trained through socialization and training activities for teachers. This activity aims to expand teacher knowledge and improve teacher skills in utilizing technology through the preparation and creation of teaching materials using the Canva application. The community service activities carried out by the PKM team of the Superior Human Resources Supporting Lecturer Program (PDPSU) at the State Elementary School located at Jl. Jawa 01, PAHANDUT, Pahandut District, Palangka Raya City, Central Kalimantan Province, have several stages, namely (1) Participation method, namely the community service team actively participates in providing knowledge socialization activities to teachers regarding the important role of teaching materials in learning, then material on how to utilize technology through the Canva application and link it to local wisdom; (2) Survey method, namely distributing questionnaires to training participants before and after implementation, as well as a satisfaction survey of community service partners and (3) Training, namely the community service team provides skills training to teachers to create teaching materials in the form of animated folk tales using the Canva application; (4) Activity Evaluation. This community service activity aims to produce innovative and creative teachers in compiling interesting teaching materials based on local wisdom. Partnership Program This activity can provide direct benefits to improving the human resources of Elementary School teachers in learning at school.